Utilization of Rice Husk Waste and Wood Powder as Filler in AC-WC Asphalt - Rizky Febrian Perdana; Bambang Supriyanto (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
With the limited natural resources, it is necessary to implement a program to reduce the use of natural resources and maximize the potential generated from unutilized waste. The types of waste that can be utilized as filler in AC-WC asphalt are rice husk ash waste obtained from Gunungsari Village, Malang Regency and sawdust ash waste obtained from H. Sulaiman Brick Factory, Malang Regency. The purpose of this research is to identify the chemical content values contained in rice husk ash and wood powder ash waste in AC-WC asphalt pavement mixtures by reviewing through marshall parameters and the Residual Strength Index (IRS). The results of the utilization of rice husk ash filler in AC-WC asphalt mixtures can provide an increase in stability values until it finally decreases at 100% content, besides that it can provide an increase in the values of yield, VIM and VMA. However, it gives a decrease in the VFA value and produces an IRS of 90.6% and can meet the requirements of Bina Marga 2018 Revision 2. In the sawdust ash filler, it can give an increase in stability and yield values until the peak at 100%, but it can give a decrease in VIM and VMA values. However, it increases the VFA value and produces an IRS of 87.2% which does not meet the guidelines of Bina Marga 2018 Revision 2.